2012
DOI: 10.2343/geochemj.2.0213
|View full text |Cite
|
Sign up to set email alerts
|

One-year monitoring of airborne radionuclides in Wako, Japan, after the Fukushima Dai-ichi nuclear power plant accident in 2011

Abstract: Airborne radionuclides from the accident of Fukushima Dai-ichi Nuclear Power Plant (FDNPP) in 2011 were measured at the RIKEN Wako Institute, Japan, about 220 km to the southwest of FDNPP, from March 15, 2011 to March 16, 2012. Radioactivity concentrations of 140 Ba, 137 Cs, 136g Cs, 134g Cs, 133g I, 132 Te, 131 I, 129m Te, 110m Ag, 99 Mo, and 95g Nb (m: metastable state; g: ground state) were determined by γ-ray spectrometry with a germanium detector. The time variations of the radioactivity concentrations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…134 Cs was detected in almost all samples, whereas before the FNPP1 accident, 134 Cs concentration was zero worldwide (e.g., Aoyama and Hirose, 2004). In addition, in all samples the activity ratio of 134 Cs to 137 Cs ( 134 Cs/ 137 Cs) was about one, which was the ratio in the radionuclides released by the FNPP1 accident, as verified by radiocesium analysis of seawater (Buesseler et al, 2011(Buesseler et al, , 2012, aerosols (Haba et al, 2012) and soil (Qin et al, 2012). Thus, there is no doubt that the radiocesium detected in the sinking particles was derived from the FNPP1 accident.…”
Section: Concentrations and Flux Of Radiocesiummentioning
confidence: 86%
“…134 Cs was detected in almost all samples, whereas before the FNPP1 accident, 134 Cs concentration was zero worldwide (e.g., Aoyama and Hirose, 2004). In addition, in all samples the activity ratio of 134 Cs to 137 Cs ( 134 Cs/ 137 Cs) was about one, which was the ratio in the radionuclides released by the FNPP1 accident, as verified by radiocesium analysis of seawater (Buesseler et al, 2011(Buesseler et al, , 2012, aerosols (Haba et al, 2012) and soil (Qin et al, 2012). Thus, there is no doubt that the radiocesium detected in the sinking particles was derived from the FNPP1 accident.…”
Section: Concentrations and Flux Of Radiocesiummentioning
confidence: 86%
“…Hirose (2012) states that "the residence times of aerosols in the troposphere, which are in the range of 5-30 d, have been determined by natural and anthropogenic radionuclides, which depend on particle size and altitude (Ehhalt, 1973)." Hirose (2012) Amano et al 2012;Haba et al 2012). However, we cannot clearly determine whether this concentration peak is due to delayed primary emission (e.g., Terada et al 2012), hemispheric circulation, or a combination of both.…”
Section: Decrease In Monthly 137 Cs Deposition After the Fdnpp Accidentmentioning
confidence: 99%
“…The pattern of domestic pollution of the land by local fallout was made fairly clear by the creation of a contamination map based on many university investigations (Kinoshita et al 2011;Tanihata 2013) and airborne surveys by Japan's MEXT and the USA's NASA/DOE (MEXT and USDOE 2011; Sanada et al 2014;Torii et al 2013;USDOE 2013). The transport of the radioactive plume and its subsequent deposition over the capital area (the Kanto Plain; Amano et al 2012;Haba et al 2012;Tsuruta et al 2014) has been reported and monitored in Tsukuba (Doi et al 2013;Kanai 2012). The MRI in Tsukuba suffered almost no electricity outage soon after the earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…However, data on 131 I are limited because of its short half life. Thus, the determination of 129 I is important as a complement to the study on the distribution of 131 I if we assume that the 129 I/ 131 I ratio emitted from the FDNPP is constant, as indicated in the 134 Cs/ 137 Cs ratio, which is almost constant at 1.0 as of March 11, 2011(Haba et al, 2012Aoyama et al, 2012).…”
mentioning
confidence: 99%